Fermentation With Pleurotus Ostreatus Enhances the Prebiotic Properties of Germinated Riceberry Rice - Soodpakdee, Kanjana; Nacha, Jutamat; Rattanachart, Nattapol; Owatworakit, Amorn; Chamyuang, Sunita (Frontiers in Nutrition, 2022)
Rice is the staple food for more than half of the world’s population. In recent years, awareness of the health benefits of colored rice varieties and germinated rice has gradually increased. Riceberry rice, a black-purple variety, was germinated and subsequently fermented with Pleurotus ostreatus mycelium to improve nutrient quality and prebiotic properties. The GABA and β- glucan contents were measured daily for a total of four days. The prebiotic activities of Riceberry rice (R), Germinated Riceberry rice (GR) and germinated Riceberry rice with mycelium (GRM) were evaluated on the probiotic bacteria Pediococcus sp., Lactobacillus acidophilus, and Streptococcus lactis. Results were compared with the P. ostreatus mycelium treatment as well as with the commercial prebiotic agents inulin, and β- glucan. The treatments were also used to evaluate inhibition of the pathogen Escherichia coli. The GABA content peaked after three days of germination. The GR sample fermented with P. ostreatus mycelium for three days had the optimal concentration of both β- glucan and GABA. Evaluation of the prebiotic properties of rice samples and the commercial standards (inulin and β-glucan) showed that these were enhanced on the GR and GRM treatments. Results also showed the improvement of prebiotic properties on Riceberry rice after germination as the Riceberry rice sample did not show any prebiotic properties in all probiotic’s bacteria while GR sample showed moderate prebiotic activity score of 0.40, 0.88 and 0.56 on Pediococcus sp., L. acidophilus, and S. lactis respectively. Furthermore, prebiotic activity of GR was improved when fermented with P. ostreatus mycelium. For further applications, the germinated Riceberry rice with mycelium could be used on rice-based products, such as rice flour, rice crackers or other rice products to enhance nutritional value and improve digestive system health especially in the elderly.